Design and synthesis of (2-(5-chloro-2, 2-dimethyl-2, 3-dihydrobenzofuran-7-yl)cyclopropyl)methanamine as a selective serotonin 2C agonist. Issue 23 (3rd June 2015) - Cheng, Jianjun; Giguere, Patrick M.; Lv, Wei; Roth, Bryan L.; Kozikowski, Alan P.
Graphical abstract: Abstract: A conformationally restricted analog of a selective cyclopropane-bearing serotonin 2C agonist was designed and synthesized. A 2, 2-dimethyl-2, 3-dihydrobenzofuran scaffold was investigated as a constrained variant of a biologically active isopropyl phenyl ether. Construction of the required dimethyl-2, 3-dihydrobenzofuran intermediate began using a procedure that relied on a microwave-assisted alkylation reaction. The synthesis of the designed compound as its HCl salt is reported in a total of 12 steps and 17% overall yield. Biological evaluation revealed the constrained analog to be a selective serotonin 2C agonist with modest potency.